A possible case of recipient anti‐neutrophil and anti‐human leukocyte antigen antibody‐mediated fatal reverse transfusion‐related acute lung injury. Issue 4 (5th March 2021) - Jug, Rachel; Anani, Waseem; Callum, Jeannie
Abstract: Background: Transfusion‐related acute lung injury (TRALI) is a transfusion complication often mediated by recipient exposure to plasma from donors with human leukocyte antigen (HLA) and human neutrophil antigen (HNA) antibodies. Recipient anti‐donor HLA or HNA antibodies have rarely been implicated. Study Design and Methods: Herein, we describe a case of fatal TRALI mediated by recipient anti‐HLA and anti‐HNA antibodies. Cognate antibody–antigen match was confirmed with serologic and molecular assays. Results: A 69‐year‐old G5P5 female with no prior transfusion history and metastatic cholangiocarcinoma with thromboembolic complications presented with heart failure and dyspnea. She was transfused 15 ml of a unit of Fy a ‐negative red blood cells and subsequently developed acute onset dyspnea, hypoxemia, hypotension, and fever. Clinical investigations revealed bilateral infiltrates on chest X‐ray and cognate recipient HLA and HNA antibodies to donor antigens. The patient died of acute respiratory failure within 24 h of transfusion. In total, the patient had Fy a, HLA Class I, HNA, and human platelet antigen (HPA) alloantibodies. The 63‐year‐old female donor had detectable HLA class II antibodies (recipient class II genotype unavailable). Conclusion: The pathophysiology of TRALI has traditionally been ascribed to underlying conditions that put the recipient at risk in combination with donor biological response modifiers. This case illustrates alternative pathogenic mediators including alloantibodies to donor HLA and HNA. Additional studies to determine the contribution and frequency of recipient alloantibodies in TRALI may inform future mitigation strategies to further reduce the incidence of TRALI, particularly in female transfusion recipients.